2020
DOI: 10.1371/journal.pone.0239557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of soil-transmitted helminthes and its association with water, sanitation, hygiene among schoolchildren and barriers for schools level prevention in technology villages of Hawassa University: Mixed design

Abstract: Background Soil-transmitted helminths (STH) remain one of the most common causes of morbidity among children in Ethiopia. Assessment of the magnitude of STH and its association with water, sanitation, and hygiene (WASH) and identify barriers for school-level prevention assist public health planners to prioritize promotion strategies and is a basic step for intervention. However, there is a lack of evidence on the prevalence of STH and its association with WASH and barriers for school-level prevention among sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…Almost all positive cases with different species of STH infections were showing the light intensity of infection that is in line with the previous report in the Gurage zone, South Central Ethiopia [35]. But other previous studies showed the occurrences of the moderate and heavy intensity of infection [18,24,29,33] other than light infection intensities; which could be the positive impact to validate for the elimination of STH infection in our country. This result is lower than the WHO elimination target of STHs, which is defined as a < 2% proportion of STH infections of moderate and heavy intensity due to A. lumbricoides, T. trichuria, and hookworm [46].…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…Almost all positive cases with different species of STH infections were showing the light intensity of infection that is in line with the previous report in the Gurage zone, South Central Ethiopia [35]. But other previous studies showed the occurrences of the moderate and heavy intensity of infection [18,24,29,33] other than light infection intensities; which could be the positive impact to validate for the elimination of STH infection in our country. This result is lower than the WHO elimination target of STHs, which is defined as a < 2% proportion of STH infections of moderate and heavy intensity due to A. lumbricoides, T. trichuria, and hookworm [46].…”
Section: Plos Onesupporting
confidence: 90%
“…These were comparable with the studies conducted in Southwest and Northwest Ethiopia [18,25]. But, the prevalence of A. lumbricoides was higher than the prevalence reported from the study conducted in Hawassa [33], Sekela [12], Ambo town [36], and Gabon (10.4%) [38]. On the contrary, it is lower than that reported from Southern Ethiopia [23,24], Western Rwanda [31], and India [32].…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…Likewise, a study at State Primary School 5 Delod Peken, Tabanan Regency, Bali Province, Indonesia, shows the most detected agent of the 105 samples of feces include Trichuris trichiura (55%) with 34.3% of children having poor personal hygiene (27). Research conducted in the Gedeo zone, Southern Ethiopia, successfully identifies characteristics of school children infected with Trichuris trichiura usually include loss of appetite, thin body, anemia, informal education of mother or caregiver, and lack or absence of school-eating program in school (28).…”
Section: Helminth Infection Agentmentioning
confidence: 99%
“…Open defecated feces will pollute the soil and environment by stools containing worm eggs. Children can become infected because they often ingest worm eggs-contaminated dirt and touch worm eggscontaminated hands (28). Primary school children who practiced open defecation in any place had twice the risk of infection than those who defecated in the family latrine (22).…”
Section: Open Defecation Behaviormentioning
confidence: 99%